Analysing refrigerant contaminants and reclamation service to prolong chiller lifespan and improving chiller energy efficiency - Li, Louis Ying Liang (2017)
From multiple industrial testing on chiller performance, refrigerant contaminants had been known as one of the main cause of efficiency loss. As the refrigerant is circulated throughout the refrigeration cycle, these efficiency loss causes great energy wastage and damage to equipment. This report studies the possible impact of contaminants in a chiller system through simulations using MATLAB Simulink. The model block built using external library Thermolib, the model consists of the compressor, evaporator, condenser and expansion valve. The refrigerant R134a was used throughout the simulations. Thermodynamic properties of the R134a such as enthalpy, heat transfer coefficient and pressure of the system were adjusted to simulate the presence of refrigerant contaminants in the system. The effect of compressor discharged temperature was also discussed in this report. Simulation results show the increase in compressor work and reduction in refrigeration effect in a contaminated system. The simulation model was able to produce results that corresponds with existing industrial study.